A systematic literature review on the impact of participation in sport and physical activities on psychological resilience - Husain, Haslinda; Samsudin, Shamsulariffin; Ayub, Ahmad Fauzi Mohd; Ahmad, Mohamad Firdaus; afwan, Nur Syazwani Zulaikha S (Intelektual Pustaka Media Utama, 2024)
Participation in sports and physical activity (PA) is often considered a potential contributor to psychological resilience due to its physical, cognitive, and social benefits. This review aims to synthesize an extensive overview of the existing knowledge landscape, shedding light on the mechanisms through which sport and PA may contribute to psychological resilience among students. Guided by the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement review method, we comprehensively searched key databases, including EBSCOhost and Scopus. Note that a total of 353 publications were initially determined. The final finding data concludes that 15 met the selection criteria. The findings were synthesized based on three themes: enhancing positive mental health, reducing negative emotions, and mitigating depression and anxiety. These outcomes highlight the transformative potential of sports and PAs in nurturing a robust psychological foundation among student populations. However, it calls for more robust and standardized research approaches. This is with implications suggesting the integration of sports and PA into comprehensive mental health programs, emphasizing their multifaceted benefits beyond psychological resilience. Tailoring interventions, recognizing the social aspects, and emphasizing the personalized approach can contribute to more effective mental health promotion strategies for students.